PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN DAN PENGUNGKAPAN MEDIA TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSRD) - Wisnu Trijaya; Ernie Riswandari (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2017)
Companies are required to realize corporate social responsibility to the public, because the company is a part of society and the environment. This study aims to describe the influence af a company size, company age and the media disclosure Disclosure of Corporate Social Responsibility (CSRD) in Indonesia. The population in this study is a mining company listed on the Indonesia Stock Exchange (BEI) in 2011-2014. Sample of companies used in this study were 13 samples by purposive sampling method. In this study, data from independent variables such as company size, company age, media disclosure  and dependent variables in the form of the Disclosure of Corporate Social Responsibility (CSRD) analyzed with descriptive analysis, classic assumption test, t-test, multiple linear regression, coefficient of determination (Adjusted R2) using SPSS 21.The results showed that company size has an influence on the disclosure of Corporate Social Responsibility ( CSRD ) with a significance value of 0.014 . Age Company has a significant value of 0.000 so this variable has an influence on the disclosure of Corporate Social Responsibility ( CSRD ) . Disclosure Media has a significance value of 0.005 so that these variables affect the disclosure of Corporate Social Responsibility ( CSRD ). Based on these results , it was concluded that all variables x ie Company Size , Age and Disclosure Corporate Media affect the disclosure of Corporate Social Responsibility ( CSRD ) . Key Words: Disclosure of Corporate Social Responsibility, Company Size, Age, Media  disclosure.